Implementing Interactive Virtual Simulation Media to Reduce Procedural Errors in Learning Motorcycle Electrical Systems in Vocational Education - Wabdillah; Nurhijrah (Journal of Vocational, Informatics and Computer Education, 2025)
This study examines changes in students’ procedural accuracy after participation in interactive virtual simulation-based learning in motorcycle electrical system instruction within vocational education. The study addresses the persistent issue of low procedural accuracy among vocational students, particularly in diagnostic sequencing, wiring interpretation, tool utilization, and troubleshooting procedures. A quasi-experimental one-group pretest–posttest design was employed involving 90 vocational students from three vocational high schools in South Sulawesi, Indonesia. Data were collected using a procedural error assessment instrument consisting of performance-based troubleshooting tasks and structured observation checklists administered under equivalent assessment conditions during the pretest and posttest. The intervention was conducted over six weeks using interactive virtual simulation media integrating guided troubleshooting procedures, visual circuit representation, and immediate corrective feedback. Data analysis included descriptive statistics, Shapiro–Wilk normality testing, paired sample t-test analysis, and Cohen’s d effect size estimation. The findings indicated substantial improvement in students’ procedural performance after participation in the simulation-based learning activities. The mean procedural accuracy score increased from 61.24 during the pretest to 82.67 during the posttest, while the average procedural error frequency decreased from 7.3 to 2.1 errors per student. The paired sample t-test revealed a statistically significant difference between pretest and posttest scores, t(89) = 18.42, p < 0.001, with a large effect size (d = 1.85). Nevertheless, because the study employed a one-group design without a control group, the findings should be interpreted cautiously and do not establish definitive causal superiority of the intervention over conventional instruction. Overall, the findings suggest that interactive virtual simulation media may support procedural learning and troubleshooting practice in vocational automotive education. The study contributes to the literature by emphasizing procedural error reduction as an important indicator of technical competency development in motorcycle electrical system learning.